Penerimaan Sistem E-Learning Pada Sekolah Menengah Kejuruan Menggunakan Technology Acceptance Model - Nining Suryani; Evy Priyanti (Universitas Bina Sarana Informatika, 2023)
The E-Learning system has begun to be implemented in every school in Indonesia as a learning medium. E-Learning is a system that uses electronic media as a learning tool, for example a smartphone or computer with an internet connection in the operating process. Of course, it is hoped that this will provide a positive role for the productivity of student learning outcomes in absorbing each lesson, and can also improve the quality of the performance of teaching teachers by using the two TAM (Technology Acceptance Model) constructs. Questionnaires were used in the method of collecting data from a population of 1200 consisting of the extended family of SMK 2 Ciputat by taking 100 respondents as a sample. The test results show that the two constructs studied have an important influence on each variable. To test whether the test device (instrument) used meets the criteria for the trial device which is adequate and appropriate, so as to create an output that is in line with what is being tested, before conducting data analysis according to the findings of the data that has been collected previously, a data test is carried out through Test Validity, Reliability, Normality, Linearity, Regression Test, and Correlation Coefficient Test and Coefficient of Determination.